Multi–agent simulation for analysing the robustness of inland container terminal networks. (18th July 2012) - Schindlbacher, Edith; Gronalt, Manfred; Hauslmayer, Hans
Using a multi–agent system, representing the nodes in the network of the Austrian inland container terminals, and using a system dynamics approach to depict the terminals' internal structures and processes in an aggregate manner, we perform network flow analyses of intermodal load units in case of unforeseen disturbances. Comprehensive case studies of disturbances and irregularities in the flow of goods in Austrian container transport chains and transport systems are the basis of the definition of several risk scenarios. These scenarios are used to investigate the robustness of the network. The simulation results show that the network under consideration has enough capacities to handle the effects of the implemented disruptions and regain initial conditions within a reasonable period of time.